The design principles of assistive courseware for low vision (AC4LV) learners - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (Asian Research Publishing Network (ARPN), 2010)
Current phenomenon faced by low vision (LV) learners is that their learning activities are problematic.With the restrictions in their vision, conventional teaching and learning techniques requires them to struggle more compared to their sighted peers.Even though Assistive Technology (AT) provides LV learners with various helpful features but most of them are in the form of hardware or software, which minimally assist the LV learners in accessing the knowledge. Meanwhile, the content applications that are specifically designed for the LV learners are highly scares. This could be seen when most of the existing content applications (i.e. courseware) that available in the market are designed for sighted students.Previous studies indicate that most of the existing courseware means too little or nothing to the LV learners especially for those who are severe.This study presents an ongoing project, with the main objective to develop an electronic learning material that focuses on content design application in an attempt to cater the needs of LV learners in their learning activities called Assistive Courseware for Low Vision Learners (AC4LV).Thus, to achieve the main objectives, this study comes out with two specific objectives which are: (i) to determine the design principles of AC4LV and (ii) to develop a prototype of AC4LV based on the gathered design principles.It is important for this study to gather information from the actual users and teachers as they are the experts in this field. Accordingly, other than document reviewed, User Centered Design (UCD) approach was utilized in gathering the inputs and comments to achieve both of the objectives.The results highlight design principles which are categorized into eight elements of AC4LV.They are justified and labeled in the form of snapshots, presented sequentially in this paper.In a nutshell, this study has achieved both of the objectives.The AC4LV has been designed according to the needs of LV learners. It has to be emphasized that the main objective of this article is to highlight the development of AC4LV and it is also important to stress that the content design of AC4LV has to refer to the determined design principles.This could be as guidance for the developer or anyone who intent to develop AC4LV.The recommended future works is to investigate the user experience of using AC4LV among the LV learners.The target participant would be the LV learners from primary school level aged nine to twelve.